Typification of Linnaean Impatiens latifolia (Balsaminaceae) - Shinde, R. D.; Singh, R. I.; Khan, S. Y.; Jadhav, J. S. (Rheedea, 2025)
Impatiens latifolia L. is nomenclaturally reviewed, compared with Impatiens bifida Thunb., and both names have been lectotypified.